Pengaruh Program Pembiaasaan 0 Jam terhadap Pembentukan Karakter Islami Siswa di SMP Ma’arif NU 2 Kemranjen - Abdul Fatah Ar Royyaan (Jurnal Budi Pekerti Agama Islam, 2025)
The background of this research is the importance of pursuing knowledge based on good morals. The formation of Islamic character based on good morals is an important aspect that needs to be emphasized in students' lives, both in the school environment and in society. This is because good character is a reflection of the success of education, especially education based on Islamic values. However, at SMP Ma'arif NU 2 Kemranjen, several student behavioral problems were still found that indicate the suboptimal formation of Islamic character. Some students appeared unprepared when submitting memorization targets (deposits), were still outside the classroom when learning began, and arrived late to participate in the 0-hour habituation program. These problems indicate the importance of evaluating the effectiveness of the 0-hour habituation program that has been implemented by the school as an effort to form Islamic character. Therefore, this study aims to determine whether there is an effect of the 0-hour habituation program on the formation of students' Islamic character. This study used a quantitative approach with a descriptive survey method. The population in this study were all 107 eighth-grade students of SMP Ma'arif NU 2 Kemranjen from three classes. Data collection techniques were conducted through documentation of the 0-hour habituation program scores given by teachers and the Islamic character formation questionnaire completed by students. The data analysis technique used was descriptive statistics, with the calculation of averages, percentages, and data categorization. The results of the study indicate that the 0-hour habituation program did not have a significant impact on the formation of students' Islamic character. Nevertheless, this program is still being implemented because it is believed to have various benefits that can support the long-term character education process. This research contributes to schools in evaluating and developing more effective strategies for forming students' Islamic character.